Divine Materiality: Peoples Temple and Messianic Theologies of Incarnation and Reincarnation - Folk, Holly (Nova religio, 2018)
This article uses archival research and personal interviews with former Peoples Temple members to explore the related ideas of incarnation and reincarnationdivine materialityas developed and taught by Jim Jones in the late 1960s and early 1970s in Peoples Temple. Jones was combinative in his understanding of his own incarnation and belief in reincarnation. He borrowed from faith healers, incorporated ideas from both New Thought and Asian religions, and found biblical justifications for his theology. Peoples Temple members accepted a variety of theological options, in what I have termed experiential pluralism, to indicate the lack of a monolithic belief system. Despite this experiential pluralism, however, reincarnation theology knit Peoples Temple members together into a community.